Corporate Governance Practices And Loan Performance Of Banks In Ghana - Sam, P.K (University of Ghana, 2016)
Corporate governance in loan administration has become a subject of sustained research interest in recent years. This study specifically examines the relationship between various variables of corporate governance practices and the loan performance of banks using loan loss provisions. Using quantitative techniques of trend analysis, regression and correlation of secondary data from the Bank of Ghana, the study looked at twenty (20) selected commercial banks in Ghana on the relationship between corporate governance and loan administration from 2006 to 2013. The results of the data are presented in statistical tables and graphs. The results show that the banking industry in Ghana was formerly dominated by four banks namely Ghana Commercial Bank (GCB), Barclays Bank Ghana (BBG), Standard Chartered Bank (SCB) and Ecobank Ghana (EBG). These banks command more than 35% of the market share. The market share of GCB, BBG and SCB dipped and banks such as Universal Merchant Bank (UMB) and the International Commercial Bank (ICB) saw negative growth in total deposits in 2012 and 2013. Also, the loan loss provisions of all the banks showed that nine (9) banks achieved a loan loss provision above the industry average of 9% as at 2013. Zenith Bank was the only bank with a loan loss provision of 9% at 2013 whilst sixteen (16) banks had a loan loss provision below the industry average as at 2013. The multivariate analysis finds that corporate governance variables of board of directors (BD), credit committee (CC), lending units (LU), relationship management (RM), credit monitoring (CM), and Bank of Ghana (BG) all have a significant impact on non-performing loans of commercial banks. The study recommends that emphasis should not only be on these explanatory variables, but on other corporate governance variables such as; insider abuse, transparency, disclosure and accountability in line with loan management.
Thesis (MPhil)
Keywords: Corporate Governance; Practices; Loan Performance; Banks; Ghana